Let a , b and c be roots of P ( x ) = x 3 + 3 x 2 + 4 x − 8 . Suppose S n = a n + b n + c n . If S 3 = 2 m + 1 and S 5 = 2 n + 1 , find the value of m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This cubic polynomial has one real root and 2 imaginary roots.
By observing the coefficients, we can observe that the real root is 1.
By using this, we can reduce the cubic to quadratic.
I used horner's method. (https://en.wikipedia.org/wiki/Horner%27s_method).
We can also take (x-1) common and get the quadratic.
So, the resultant quadratic is x 2 + 4 x + 8 . It is of the form,( l x 2 + m x + n . where l =1, m=4, n=8.
In the above quadratic, determinant\(m^{ 2 }-4ln) is less than zero, So, the roots are complex.
Now the main key points are sum of roots and product of roots. Let us consider 1 as a. Then the remaining roots are b and c.
b+c = -4 and bc = 8. Using this we can find S(3) and S(5).
S(3) :- .
\({ a }^{ 3 }+{ b }^{ 3 }+{ c }^{ 3 }={ { 1 }^{ 3 }+(b+c) }^{ 3 }-3ab(a+b)\quad =\quad 1-64+96\quad =\quad 1+{ 2 }^{ m=5 }\).
S(5):-.
a 5 + b 5 + c 5 = 1 5 + ( b 3 + c 3 ) ( b 2 + c 2 ) − b 2 c 2 ( b + c ) = 1 + 3 2 × 0 − ( − 2 5 6 ) .
= 1 + 2 n = 8 .
Thus, m=5 and n=8 and m+n=13.
Note:- ( b 2 + c 2 ) = ( b + c ) 2 − 2 b c = 1 6 − 1 6 = 0 . .
Hey , you can do it by N e w t o n ′ s s u m s also and it will take less time.
its easy to note
a + b + c = − 3
a b + b c + c a = 4
a b c = 8
we would get
a 2 + b 2 + c 2 = 1
and then
a 3 + b 3 + c 3 = 3 3
thus m = 5
and using long calculation
a 5 + b 5 + c 5 = 2 5 7
thus n = 8
Try it with NEWTON's SUMS METHOD also as it requires less calculation.
Log in to reply
Bro. Please provide a link to know about Newton sum.
Problem Loading...
Note Loading...
Set Loading...
Let P 1 = a + b + c , P 2 = a b + b c + c a and P 3 = a b c . Using Vieta's formulas, we have P 1 = − 3 , P 2 = 4 and P 3 = 8 .
Now, using Newton sums method, we have:
S 1 S 2 S 3 S 4 S 5 = P 1 = − 3 = P 1 S 1 − 2 P 2 = ( − 3 ) ( − 3 ) − 2 ( 4 ) = 1 = P 1 S 2 − P 2 S 1 + 3 P 3 = ( − 3 ) ( 1 ) − 4 ( − 3 ) + 3 ( 8 ) = 3 3 = 2 5 + 1 = P 1 S 3 − P 2 S 2 + P 3 S 1 = ( − 3 ) ( 3 3 ) − 4 ( 1 ) + 8 ( − 3 ) = − 1 2 7 = P 1 S 4 − P 2 S 3 + P 3 S 2 = ( − 3 ) ( − 1 2 7 ) − 4 ( 3 3 ) + 8 ( 1 ) = 2 5 7 = 2 8 + 1
⇒ m + n = 5 + 8 = 1 3